PERUMUSAN STRATEGI BISNIS UNTUK MERAIH KEUNGGULAN BERSAING - Rofiq, Ahmad Faiqun Nawwar; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to analyze the formulation of the correct business strategy for Raos Abadi, a bean curd producing company, so it can have some competitive advantage over other similar companies. This qualitative descriptive research starts by identifying and analyzing the internal and external environmental factors of the company. Then, the results of the identification and analysis were processed using IFE (Internal Factor Evaluation) matrix, EFE (External Factor Evaluation) matrix, SWOT (Strength, Weakness, Opportunity, Threats) matrix, and IE matrix. This study finds that the internal environmental factor of Raos Abadi consists of four strengths and four weaknesses, while its external factor consists of four opportunities and four threats. Then, using SWOT and IE matrix, the company is advised to apply hold-and-maintain strategy through market penetration and product development. The penetration can be done by increasing promotion cost, intensifying promotions in social media, and expanding its agency network in more places. Then, product development can be carried out by keeping informed about and anticipating competitors’ sales strategy, improving the quality of the existing products, and innovating for new products.